Improving Students’ Reading Comprehension by Using SQ3R Method - Syahfutra, Wandi (Journal of English and Arabic Language Teaching, 2017)
Reading is one of the most important components of any language and it is an essential tool  for  long-life  learning.  The  goal  of  reading  is  comprehension.  In  order  to comprehend reading passage, students need to apply some methods to help them. This study aimed at improving students’ reading comprehension and motivation by using SQ3R method. SQ3R system has been used successfully for many years and the system has proven effective in increasing students’ retention. Student learning centres on a complex problem that does not have a single correct answer. Students work in collaborative  groups  to  identify what  they need  to  learn  in  order to improve their reading comprehension.. From the test, it was obtained that the lower score is 64 and the higher score is 88. The mean is 81.03. The data were obtained from the research by using SPSS. Overall, the results showed that students’ reading comprehension could be improved by using SQ3R method were identified.